Optimization of glycerol recovery on effect of waste volume and ph using response surface methodology (RSM) - Mohd Syahrul Ridhwan, Abdullah (2011)
Biodiesel waste or glycerol residue is a byproduct from transesterification of vegetable oil to biodiesel. These wastes contain high percentage of glycerol and other impurities such as salt and ash produced during production of biodiesel. Recovery of glycerol from biodiesel waste can give positive impact to the environment and very economical. The main objective of this experiment is to optimize the effect of glycerol residue (waste) volume and effect of pH on the glycerol production using Response Surface Methodology (RSM) based on central composite design (CCD). Pretreatment of glycerol residue is using sulphuric acid and then follow by neutralization using natrium hydroxide and evaporation process to concentrate the recovered glycerol. Every steps in pretreatment process, the glycerol recovered is filtered in order to remove the impurities. The experiment had been run with nine different pH from pH 1 t0 pH 9 and different volume of sample from 80 ml to 160 ml of glycerol residue. The optimized condition for highest recovery of glycerol is 138.78 ml of waste volume and pH at 4.71. The glycerol recovered at optimum condition is 8.656 g/l. for conclusion, the effect of ph and waste volume give significant effect to the concentration of glycerol recovered.